A chelate like no other: exploring the synthesis, coordination chemistry and applications of imidoyl amidine frameworks. Issue 8 (7th November 2020) - Kitos, Alexandros A.; Mavragani, Niki; Murugesu, Muralee; Brusso, Jaclyn L.
Abstract : Exploration of imidoyl amidine based materials in organic and inorganic chemistry demonstrates the vast applicability of these highly versatile frameworks. The account provides a critical overview of research progress on the chemistry and complexation of these ligands. Abstract : Since the remarkable work by Werner, the design and use of chelating ligands have played an essential part in coordination chemistry. While ligands such as 2, 4-pentanedione (acac) and 1, 5-diazapentadienyl (NacNac) have been established in the literature for over a century and their rich coordination chemistry is well known, 1, 3, 5-triazapentadiene ligands remain the significantly less explored members of this family. Also known as imidoyl amidine (ImAm ), the coordination chemistry of this ligand framework has recently attracted a great deal of attention due to its multiple binding sites, ability to be incorporated into organic and inorganic materials, and diverse applicability (catalysis, biomolecular probes, materials science, etc. ) making them a class of chelates like no other. The scope of this review is to provide a critical overview of the research progress on the chemistry of ImAm as well as complexation with different metal ions. General synthetic routes and new insights for the preparation of ImAm are discussed along with their use as starting materials or intermediates in organic and coordination chemistry in the development of materials that have found use in fields ranging from magnetic, conducting and luminescent materials to catalysis and biomedical applications. Concluding remarks including the limitations and perspectives of ImAm are discussed.